Mechanical and Self-Sensing Properties of Multiwalled Carbon Nanotube-Reinforced ECCs - Chuanbo Liu; Guozhen Liu; Zhi Ge; Yanhua Guan; Zhiyong Cui; Jian Zhou (Advances in Materials Science and Engineering)
This paper investigates the effect of type and dosage of multiwalled carbon nanotubes (MWCNTs) on the mechanical and self-sensing properties of engineered cementitious composites (ECCs). Two types of MWCNTs (MWCNTa and MWCNTb) were employed. The tensile and flexural strengths of CNT-reinforced ECCs were improved compared with normal ECCs, while the ultimate tensile strain and midspan deflection were reduced. Compared with the dosage of MWCNTs, the type had less effect on these properties. The percolation threshold was around 0.3 wt.%. ECCs containing MWCNTs had good self-sensing ability under different loading conditions. When the midspan deflection increased from 0.1 to 0.6 mm, the fractional change in resistivity reached 9%. The dosage of MWCNTs had a significant effect on the self-sensing ability. As the MWCNT content increased, the amplitude of fractional change in resistivity decreased.